Valuation of Energy Security for Natural Gas—European Example - Piotr Kosowski; Katarzyna Kosowska (Energies, 2021)
Recently there has been an ongoing discussion about energy security. This has been caused by tensions affecting international relations, and the emergence of new geopolitical threats. As one of the main sources of primary energy, natural gas is an obvious subject of interest in this discussion. In Europe, the natural gas market is rapidly evolving, which has resulted in a lack of clarity regarding who is responsible for the security of the gas supply. It is not clear now how to measure the security of the gas supply in economic estimates and by whom that security should be financed. In this paper, the authors present an approach which can be used for valuation of energy security concerning the security of natural gas storage using stochastic modelling based on the mathematical model of the “Newsvendor problem”. The valuation is made from the point of view of countries and considers their individual attitudes to the risk of disruption of deliveries, which is a novel approach to the problem. The authors believe that the current level of storage capacities, as compared to the demand for natural gas, can show the attitude of each country to the risk and potential cost of stockout. In line with this belief, the target value in the model is not the optimal level of inventory, but the cost of stockout. The results show significant variations in the assessment of the risk. The future of natural gas as an important fuel and source of primary energy in Europe is not clear and unfavorable changes have been sped up by the COVID-19 pandemic. Gas (energy) companies in Europe are turning to decarbonization and green energy, and the pandemic has accelerated these changes. European energy companies used to see the use of natural gas as a transition fuel and a key component of their long-term decarbonization strategies, but now they are switching to multi-energy models through massive investments in renewables and hydrogen. Experts expect that gas will remain an important part of Europe’s energy supply, but it may be gradually replaced by hydrogen and renewables.